Kunci Peningkatan Produktivitas Melalui Pemberdayaan Karyawan - Wiswina Waruwu; Idah Kusuma Dewi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze key factors driving productivity improvement through employee empowerment at PT. TI Matsuoka Winner Industri, a Japanese-owned garment factory in Semarang focused on export production. Employing a qualitative approach with a case study design, the research involved five informants: a manager, a supervisor, a quality control employee, and two sewing operators. Data were collected through in-depth interviews, participant observation, and document analysis, then analyzed using thematic analysis techniques. The findings reveal that employee empowerment practices remain at an early developmental stage and are inconsistently implemented across production divisions (cutting, sewing, finishing, and quality control). Major barriers include a hierarchical organizational culture, resistance from mid-level supervisors, limited information technology support, strict export deadlines, and seasonal demand fluctuations. The study highlights that employee empowerment depends not only on managerial policy but also on organizational culture and system readiness. This research contributes to the literature on employee empowerment in Indonesia’s export-oriented garment industry and provides strategic recommendations for management to build a sustainable empowerment system through cultural transformation, leadership competency development, technology optimization, and alignment of performance management with human resource development within a highly competitive global production environment.